O efeito da governança corporativa na previsibilidade dos modelos de perda com crédito dos bancos brasileiros listados na B3 - Brasil, Carolina Machado (2024)
Banks constitute credit losses to cover the credit risk to which they are exposed in their operations. Credit losses represent banks' largest accrual and are measured using models. Brazilian banks disclosed financial statements using the expected loss model (IFRS 9) and the mixed model (BRGAAP). As it is a subjective measurement, credit losses depend on the judgments, at some level, of managers. Therefore, regardless of the loss model used, it is important to limit the power of managers in this estimation so that the information provided is more reliable. Efficient corporate governance mechanisms can contribute to the disclosure of more useful information. Specifically, given their responsibilities, the board of directors and supervisory and control bodies (audit committee, fiscal council, internal audit, independent audit and compliance) can act to improve the quality of accounting information. The purpose of credit losses is to highlight future write-offs. Therefore, a greater association between credit losses and future write-offs should imply a higher quality of accounting information. The study aimed to analyze the effect of corporate governance on the predictability (association of credit losses and future write-offs) of Brazilian banks' credit loss models. The sample considered 91 observations from Brazilian banks listed on B3 in the period from 2018 to 2021 considering both BRGAAP and IFRS statements. Corporate governance was measured based on an index constructed considering the information provided in the Brazilian Corporate Governance Code Report, for the principles of the board of directors and supervisory and control bodies. The results showed that: i) higher quality corporate governance improves the redictability of credit losses when considering the expected loss model (IFRS 9), with no effect shown for the mixed model (BRGAAP); ii) the mixed model (BRGAAP) presents a greater predictability of credit losses than the expected loss model (IFRS 9); and iii) higher quality corporate governance acts to reduce the difference between the predictability of credit loss models. The results indicated that more effective corporate governance, translated into greater adoption of corporate governance practices for the board of directors and supervisory and control bodies defined in the Brazilian Code of Corporate Governance, are efficient in improving the predictability of losses with credit and in reducing divergences in predictability between credit loss models with different levels of freedom of judgment. Therefore, regardless of the credit loss model used by banks, the adoption of best 910 corporate governance practices positively influences the quality of accounting information.